2022
DOI: 10.35409/ijbmer.2022.3407
|View full text |Cite
|
Sign up to set email alerts
|

A Coherency of Transformational Leadership, Organizational Commitment, and Employee Performance

Abstract: Higher education plays an important role and has become a priority in creating and enhancing skills in developing countries. However, there are many challenges and problems faced in carrying out educational visions. This study was to investigate the coherency of transformational leadership, organizational commitment, and employee performance. This study uses a quantitative method with the questionnaire administered to collect data from 120 employees at the ministry of higher education at Timor Leste, using Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Both of these values have met the conditions for H3 acceptance (0.000<0.05), meaning that leadership style influences commitment. (Surya, Piedade and Riana, 2022) are following this study and found that leadership style affects commitment. The difference findings between this study and (Surya, Piedade and Riana, 2022), is that leadership style is not proven to improve employee performance.…”
Section: H3: Leadership Style On Commitmentmentioning
confidence: 79%
“…Both of these values have met the conditions for H3 acceptance (0.000<0.05), meaning that leadership style influences commitment. (Surya, Piedade and Riana, 2022) are following this study and found that leadership style affects commitment. The difference findings between this study and (Surya, Piedade and Riana, 2022), is that leadership style is not proven to improve employee performance.…”
Section: H3: Leadership Style On Commitmentmentioning
confidence: 79%
“…Employee performance is a crucial factor that contributes to the success of an organization in navigating global competition (Sinambela & Sinambela, 2019). It is the outcome of the efforts of individuals or groups within an organization, who work within their designated roles and responsibilities to achieve the organization's goals in a legal, ethical, and morally upright manner(Ketut Surya et al, 2022).…”
Section: Employee Performancementioning
confidence: 99%
“…Transformational leadership, which emphasises vision, motivation, and staff development, is believed to have the ability to bring about substantial changes in corporate culture andperformance. Transformational leadership refers to the process in which a leader motivates and empowers their subordinates to beyond their own expectations and personal interests in order to benefit the organisation (Ketut Surya et al, 2022;Manik, 2016).…”
Section: Introductionmentioning
confidence: 99%